2019
DOI: 10.3846/mbmst.2019.091
|View full text |Cite
|
Sign up to set email alerts
|

Modal passport of dynamically loaded structures: application to composite blades

Abstract: Close relation of modal properties to mechanical properties of structures presents interest for applied research and solutions of Structural Health Monitoring (SHM) tasks. The paper considers application of analytical and modal analysis techniques for structural research and monitoring of composite blades as well as required measurement tools. The Roving Hummer Technique (RHT) and Operational Modal Analysis OMA) were admitted as optimal methods for modal properties estimation, but 3-axial accelerometers and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The latter is not thicker than the films/wires and smooths out the roughness. Trial applications of piezo films into composite blades [ 19 , 26 , 27 ] demonstrated workability of such technical solutions in operational conditions. For instance, the measurement system remained functional at rotating frequencies up to 25 rev/sec, with no discernible effect on the aerodynamic profile.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is not thicker than the films/wires and smooths out the roughness. Trial applications of piezo films into composite blades [ 19 , 26 , 27 ] demonstrated workability of such technical solutions in operational conditions. For instance, the measurement system remained functional at rotating frequencies up to 25 rev/sec, with no discernible effect on the aerodynamic profile.…”
Section: Methodsmentioning
confidence: 99%
“…For a test case, the typical testing procedure, which simulates ambient excitation, complements the recording procedure. The typical OMA [ 19 ] algorithms 3 are used to estimate the modal parameters from the sensor signals. These algorithms, which are realized by some OMA estimators in Frequency and Time Domains, compute the modal parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, an operator estimates the modal parameters of the structure. The resulting parameters together with the possible external operational factors, such as static loads, temperature or speed of rotation (blades), are input to a modal passport [21,22], where the past measurements are stored. Modal parameters in a reference or intact structural state together with their deviations due to operational factors form a "signature" of a structure that is unique to this structure or for structures of this type.…”
Section: Damage Detection Algorithmmentioning
confidence: 99%